Accommodation Strategies for Health Sciences Students with Disabilities. - JACKSON, VERONICA; HENDERSON, DEANNA L.; EDWARDS, JR., DOTHEL W.; RAINES, GRESHUNDRIA M. (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
The Rehabilitation Act of 1973 and Americans with Disabilities Act of 1990 have increased educational and employment opportunities for students with disabilities. These regulations protect individuals who are seeking higher education. Admissions committees of health science professional programs must consider these regulations when developing admissions criteria, academic curricula, clinical internships, and employment opportunities. Students cannot be denied access to education at a public-serving entity that receives federal funding. Students who have documented disabilities have the burden to safely perform an educational program's requirements, and faculty must take an active role in facilitating accommodation strategies for them. This paper considers accommodation strategies for admissions, academic curricula, clinical internship placement, and employment.